2018
DOI: 10.1111/1467-9817.12264
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of the organisational arrangements of primary school‐based reading interventions for struggling readers

Abstract: This paper presents findings from a systematic literature review that explored the delivery arrangements of school-based reading interventions for struggling readers aged 5-8 years. Databases were searched for published and unpublished studies from 1970 to 2017, which employed a randomised controlled trial or quasi-experimental design. Sixty-four texts that met the inclusion criteria were categorised according to targeted tier based on the response-to-intervention model. Findings showed that tier 2/3 intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Based on a literature review regarding school-based reading interventions, studies showed that there was a lack of classroom aids in some schools, in addition to a resistance from teachers due to higher workloads. It was proposed that more practical methods of intervention should be used for it to be feasible for teachers who don't have teaching assistants (Stentiford, Koutsouris, and Norwich, 2018).…”
Section: Advantages Negative Criticisms and Challenges Of Leveled Readingmentioning
confidence: 99%
“…Based on a literature review regarding school-based reading interventions, studies showed that there was a lack of classroom aids in some schools, in addition to a resistance from teachers due to higher workloads. It was proposed that more practical methods of intervention should be used for it to be feasible for teachers who don't have teaching assistants (Stentiford, Koutsouris, and Norwich, 2018).…”
Section: Advantages Negative Criticisms and Challenges Of Leveled Readingmentioning
confidence: 99%
“…Based on a literature review regarding school-based reading interventions, studies showed that there was a lack of classroom aids in some schools, in addition to a resistance from teachers due to higher workloads. It was proposed that more practical methods of intervention should be used for it to be feasible for teachers who do not have teaching assistants (Stentiford, Koutsouris, and Norwich, 2018).…”
Section: Negative Criticism and Challengesmentioning
confidence: 99%
“…Studies revealed that teachers resist certain intervention strategies because they can be timeconsuming and result in a higher workload. Moreover, not all teachers are equipped with the proper training that will allow them to conduct the specific reading assessments that come with leveling reading (Stentiford, Koutsouris, and Norwich, 2018). Furthermore, the OECD released an evaluation report of schools in the UAE where it was revealed that school principals reported more staff shortage and less material shortage than the OECD average (Organisation for Economic Co-operation and Development, 2018).…”
Section: 2(a) Teachers' Surveymentioning
confidence: 99%
“…A systematic review of 64 international experimental evaluations between 1970-2017 focussed on how school-based reading interventions for struggling readers aged 5-8 years were delivered in a wave / tier 2 or targeted form by the RTI model (Stentiford, Koutsouris and Norwich, 2018). The review showed that the wave 2/3 interventions targeting pupils who did not respond to whole class teaching (wave / tier 1) were almost all delivered in pull-out sessions by people other than the classroom teacher.…”
Section: Conceptualising Igr As An Inclusive Targeted Interventionmentioning
confidence: 99%